Programme Planning Practices in Continuing Professional Education in Selected Professional Associations in Malaysia - Ong, Mek Hiok (2008)
The purpose of this study is to examine the process of programme planning in the selected continuing professional education providers in Malaysia. It specifically examines how programme planners design and plan CPE activities and what contextual influence these practices. The study also examines how planners negotiate these influences and how this affected their planning practice. The following research questions guides the study: 1. How do programme planners in the selected professional associations design and develop continuing professional education? 2. What are the contextual factors influencing the continuing professional educational programme planning practices in the selected providers? 3. Is programme planning a social activity in which interests are negotiated by planners in the context of the organization structured by power relations? The study employed the qualitative multiple case study approach and data were collected through in-depth interviews and examination of relevant documents. Three professional associations, from the accounting, medical, and the architectural professions were purposefully selected for this study. Six programme planners, two from each provider were interviewed on the programme planning practices that they carried out in their respective associations. Their interviews were taped recorded and transcribed. A constant comparative method was used in the within-case and cross-case data analysis. A framework of programme planning practices in continuing professional education in the selected professional associations in Malaysia was developed based on the eight themes that emerged from the data analysis. The eight themes are: (1) Initiation of Ideas, (2) Selection of Topics, (3) Identification of Speakers, (4) Development of Content, (5) Arrangment of Facilities, (6) Marketing, (7) Conducting the Programme, and (8) Evaluation of Programme. The study also revealed three contextual factors that influence programme planning practices in the selected providers and they are: policy on continuing professional education regulation, organizational power structure, and commercial support. The study also confirmed that programme planning is a social activity that requires planners to negotiate personal and institutional interests when developing programmes, and negotiations occur within the context of the organization structured by asymmetrical power relationships. Three conclusions were drawn from the study. (1) The framework developed from description of the programme planning practices in the three selected professional education providers resembles that of the classical model but is very simplistic and not systematic in nature. (2) The three contextual factors that emerged from the data were interconnected in influencing the programme-planning practices in the selected providers. (3) The findings of the study confirmed that programme planning is a social activity that requires planners to negotiate personal and institutional interests when developing programmes and negotiations occur within the context of the organization structured by asymmetrical power relationships.